Global Health Warning: Definitions Wield Power; Comment on "Navigating Between Stealth Advocacy and Unconscious Dogmatism: The Challenge of Researching the Norms, Politics and Power of Global Health" - Robert Marten (Kerman University of Medical Sciences, 2016)
Gorik Ooms recently made a strong case for considering the centrality of normative premises to analyzing and understanding the underappreciated importance of the nexus of politics, power and process in global health. This critical commentary raises serious questions for the practice and study of global health and global health governance. First and foremost, this commentary underlines the importance of the question of what is global health, and why as well as how does this definition matter? This refocuses discussion on the importance of definitions and how they wield power. It also re-affirms the necessity of a deeper analysis and understanding of power and how it affects and shapes the practice of global health.